2020
DOI: 10.1007/s10389-020-01329-5
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors of COVID-19 spreading: a case study of Thailand

Abstract: Aim A novel corona virus disease 2019 was declared as pandemic by WHO as global level and local levels in many countries. The movement of people might be one influencing factor, this paper aims to report the situation COVID-19 and spreading in Thailand, including influencing factors of spreading and control. Subject and method Infected, confirmed COVID-19 data were obtained from the official website of the Department of Disease Control, Ministry of Public Health. Tourist data was downloaded from Ministry of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 11 publications
3
68
0
4
Order By: Relevance
“…The study finds significant effect of poverty incidence and proportion of elderly (65+ years) people on COVID-19 risk. The results on effect of poverty on COVID-19 risk are consistent with the literature ( Tantrakarnapa, Bhopdhornangkul & Nakhaapakorn, 2020 ; Sarmadi et al, 2020 ), where it was found that high income compared to low income was positively associated with COVID-19 cases. Low risk of COVID-19 among poor people than rich people may be due to the fact that such people are less likely to travel to cities and abroad where they can be exposed to the disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study finds significant effect of poverty incidence and proportion of elderly (65+ years) people on COVID-19 risk. The results on effect of poverty on COVID-19 risk are consistent with the literature ( Tantrakarnapa, Bhopdhornangkul & Nakhaapakorn, 2020 ; Sarmadi et al, 2020 ), where it was found that high income compared to low income was positively associated with COVID-19 cases. Low risk of COVID-19 among poor people than rich people may be due to the fact that such people are less likely to travel to cities and abroad where they can be exposed to the disease.…”
Section: Discussionsupporting
confidence: 91%
“…The spread of COVID-19 is driven by environmental factors like temperature and humidity, where cases spike with low temperature and humidity ( Mecenas et al, 2020 ; Eslami & Jalili, 2020 ; Bherwani et al, 2020 ). Demographic and socioeconomic factors like population density, age distribution, income, number of tourists, also play a role in the spread of COVID-19 cases, where high cases are observed with high density, age, income and large number of tourists ( Tantrakarnapa, Bhopdhornangkul & Nakhaapakorn, 2020 ). Density has also been found not to be correlated with COVID-19 cases ( Hamidi, Sabouri & Ewing, 2020 ), contrary to the belief of many that it is positively correlated with COVID-19 cases.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the number of imported cases can affect the magnitude of an outbreak [ 39 ]. In Thailand, the number of confirmed cases was strongly associated with the number of tourists and their activities [ 40 ]. Therefore, interventions such as travel bans, closing the border, and the 14-day state or alternative quarantine for international travellers should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Rate of infection and the fast transmission of the disease is one of the alarming issues of the pandemic. In Thailand, the number of tourists and their activities were found to be significant factors on the number of infected patients from COVID-19 [ 31 ]. In Italy, a tighter lockdown, mobility decreased enough to bring down transmission promptly below the level needed to sustain the epidemic [ 32 ].…”
Section: Introductionmentioning
confidence: 99%